SPECIAL FEATURES OF REHABILITATION AND OUTCOME PREDICTION IN MYOCARDIAL INFARCTION COMPLICATED BY ARRHYTHMIAS - N. I. Tarasov; V. N. Karetnikova; E. V. Malahovich; B. Z. Zhaleyev; E. N. Gulyayeva; O. L. Barbarash (Российский кардиологический журнал)
We have studied the special features of rehabilitation and long-term (1 year) prognosis in 92 patients with myocardial infarction complicated by disturbances of heart rhythm and conduction within the first 48 hours.Veloergometric test, Holter monitoring and echo were preformed in 2 weeks and 12 months after the onset of the MI, in order to determine the status of the coronary flow, coronary reserve and LV contractile reserve.We have shown that transient disturbances of heart rhythm and conduction have no significant impact at the clinical course, and the duration of hospital-stage rehabilitation of 14-18 days may suffice in this category.